A Numerical Simulation of the Effect of Buffer Layer Band Gap on the Performances of nc-Si : H Based Solar Cells - H. Touati; B. Amiri; A.C. Sebbak; A. Benameur; H. Aït-kaci (Журнал нано- та електронної фізики)
This paper describes an investigation, by using numerical simulation, into the impacts of i-nc-Si : H buffer layer band gap on the photovoltaic parameters of n-i-p hydrogenated nanocrystalline silicon (nc-Si : H) solar cells. The output external cell parameters, like, the short-circuit current (JSC), the open circuit voltage (VOC), the fill factor (FF) and efficiency (Eff) are simulated by varying the mobility band gap (Eg) of i-nc-Si : H buffer layer. Also, the band diagram of nc-Si : H n-i-p solar cell, the electric field and the traped hole density at i/p interface, and the external quantum efficiency, with different values of buffer layer band gap where optimized. The simulation result shows that in valence band and for both interfaces, the band offsets ΔEV1 at p-nc-Si : H (window layer) / i-nc-Si : H (buffer layer) and ΔEV2 at i-nc-Si : H (buffer layer) / i-nc-Si : H (absorber layer) can be affected by varying Eg. It is obtained that the values efficiency are 10.89 % and 11.33 % when the value of i-nc-Si : H buffer layer band gap are 1.4 eV and 1.55 eV, respectively. However, the i-nc-Si : H buffer layer band gap of 1.55 eV was optimized for obtaining a better efficiency for n-i-p solar cell based on hydrogenated nanocrystalline silicon.